2010
DOI: 10.1111/j.1742-4658.2009.07556.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological truncation and domain organization of a novel uracil‐DNA‐degrading factor

Abstract: Uracil in DNA is usually considered to be an error, but it may be used for signaling in Drosophila development via recognition by a novel uracil‐DNA‐degrading factor (UDE) [(Bekesi A et al. (2007) Biochem Biophys Res Commun355, 643–648]. The UDE protein has no detectable similarity to any other uracil‐DNA‐binding factors, and has no structurally or functionally described homologs. Here, a combination of theoretical and experimental analyses reveals the domain organization and DNA‐binding pattern of UDE. Sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…6). This result suggests that folding is not much perturbed by the C-terminal truncation, in agreement with a recent study showing a high degree of disorder in the C-terminus [13]. A very different short cluster of nonpolar and basic residues (PAAKKMKID), present on the long isoform of D. melanogaster dUTPase, was found to perovide highly efficient NLS function in the dUTPase protein.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6). This result suggests that folding is not much perturbed by the C-terminal truncation, in agreement with a recent study showing a high degree of disorder in the C-terminus [13]. A very different short cluster of nonpolar and basic residues (PAAKKMKID), present on the long isoform of D. melanogaster dUTPase, was found to perovide highly efficient NLS function in the dUTPase protein.…”
Section: Discussionsupporting
confidence: 90%
“…In D. melanogaster, two physiological isoforms of the enzyme were identified, with apparent molecular masses of 69 and 63 kDa for the native homotrimers (termed long isoform, LD-DUT, and the N-terminally truncated short isoform, NTT-DUT, respectively) [27]. Only LD-DUT contains the complete putative NLS sequence [PAAKKMKID (10)(11)(12)(13)(14)(15)(16)(17)(18)], while NTT-DUT lacks 14 residues at the N-terminus. This segment shows a high degree of flexibility and cannot be located in the 3D structure of the protein determined by X-ray crystallography (PDB ID 3ECY) [21]).…”
Section: Introductionmentioning
confidence: 99%
“…This situation, together with the lack of dUTPase, which is responsible for preventing thymine‐replacing uracil incorporation into DNA, in larval tissues may allow accumulation of uracil‐containing DNA at least at specific developmental stages [6]. By the use of affinity chromatography for searching additional uracil‐DNA‐recognizing factors in late larval extracts, a specific uracil‐DNA‐degrading protein (UDE), with homologues only in pupating insect genomes, was identified and partially characterized [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…De novo 3D modelling of the 1A/1B fragments revealed the existence of two helical bundles with an extended surface formed by conserved positively charged residues [8]. These results, together with DNA‐binding‐induced protection against limited proteolysis, suggested that DNA binding may occur in this region [8]. Detailed characterization of the interaction between UDE and nucleic acids is expected to provide important insights into specific aspects of the novel activity.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it may be relevant to mention that in vertebrate B cells, scheduled appearances of uracil in DNA and their subsequent processing by UNG were shown to be involved in immunoglobulin gene diversification. 35 In lack of UNG in Holometabola insects, it remains to be determined which enzymes may play physiologically significant roles in uracil-DNA processing (other uracil-DNA glycosylases such as TDG or SMUG homologs 36 or different proteins, cf [37][38][39] ). Identification of putative Holometabolaspecific uracil-DNA processing pathways may be of importance not only for Drosophila melanogaster as a model organism but also for Anopheles species, involved in several infectious diseases.…”
Section: The Case Of Drosophila Melanogastermentioning
confidence: 99%